Thermodynamics of a time-dependent and dissipative oval billiard: A heat transfer and billiard approach - Leonel, Edson D. [UNESP]; Galia, Marcus Vinícius Camillo [UNESP]; Barreiro, Luiz Antonio [UNESP]; Oliveira, Diego F. M. (American Physical Society (APS), 2016)
We study some statistical properties for the behavior of the average squared velocity - hence the temperature - for an ensemble of classical particles moving in a billiard whose boundary is time dependent. We assume the collisions of the particles with the boundary of the billiard are inelastic, leading the average squared velocity to reach a steady-state dynamics for large enough time. The description of the stationary state is made by using two different approaches: (i) heat transfer motivated by the Fourier law and (ii) billiard dynamics using either numerical simulations and theoretical description.